The influence of High tibial osteotomies on the posterior tibial slope - Study of 190 medial open wedge and 89 lateral closed wedge cases. Issue 5 (28th May 2020) - Schubert, Ilona; Ferner, Felix; Strohm, Peter; Dickschas, Jörg
Aims and Objectives: High tibial osteotomies (HTO) are nowadays an established method to treat unicompartmental, medial gonarthrosis. Common surgical HTO techniques include medial open wedge (MOW) and lateral closed wedge osteotomies (LCW). In addition to the intended change in the frontal plane these surgical techniques take influence on various other biomechanical issues of the knee joint e.g. the posterior tibial slope (PTS). Aim of this study was to rate and evaluate changes of the tibial slope by HTOs dependent on the used surgical technique (MOW versus LCW). Materials and Methods: 414 HTOs, that had been performed in our institution between 2004 and November 2018, were reviewed retrospectively. 135 cases were excluded. The included 279 cases from 247 patients were divided into two groups dependent on the used surgical technique (MOW/LCW). In both groups the values of PTS were defined by measuring the proximal posterior tibia angle (PPTA) on lateral x-rays of the knee from before and 4 to 6 weeks after surgery. The change of PTS was evaluated as delta-PPTA. Microsoft Excel was used for statistical analysis. Results: 279 cases were included: 190 were assigned to the group of MOW and 89 to the group of LCW osteotomies. Considering demographic data the MOW-group showed a gender distribution of 124 men/ 46 women in 93 left and 97 right knees, and the LCW-group of 46 men/43 women in 40 left and 49 right knees. The mean value of age in the MOW group was 47, 6 +/- 10 years (15-70 years) and in the LCW-group 40, 6+/-13, 7 years (15-67 years). Before surgery there was no statistical significant difference in the PPTA-values between both groups (p=0, 720): The mean PPTA in the MOW-group measured 79, 9°+/-3, 2° (68-88°), in the LCW-group 80, 6°+/-2, 6° (74-88°). The change caused by surgery showed no statistical significance in the MOW-group (delta-PPTA 0, 07°+/- 2, 9° [-12° bis 11°]). However, in the LCW-Gruppe we observed a significant (p<0, 001) decrease of the PTS (delta-PPTA -3, 09°+/- 4, 5° [-12°bis 5°]). Nevertheless, the analysis of delta-PPTA in the LCW-group over the timeline of the study period showed tendencies of a decline of slope-reduction. Conclusion: As the PTS plays a relevant role in biomechanics of the knee joint a consideration of the impact of changes in PTS by HTOs is indispensable. Our results support the common thesis of a slope-reduction by LCW osteotomies but nevertheless the analysis throughout the study period showed a reduction of the slope-decrease over timeline. The common thesis of a slope-increase by MOW osteotomies was not supported by our results which showed no significant change.